Pengaruh Content Marketing Dan Brand Image Terhadap Keputusan Pembelian Produk Skintific - Arni Ramdaniati; Intisari Haryanti; Muhajirin Muhajirin (JURNAL DIMENSI, 2026)
This study analyzes the influence of content marketing and brand image on Skintific Cushion purchase decisions in Bima City, NTB. Background: Indonesia's booming skincare industry where consumers select makeup-skincare hybrids like Skintific promoted by influencers on social media. Independent variables: content marketing (relevance, info quality, consistency, attractiveness, interactivity); brand image (association, uniqueness, superiority, trust, reputation). Dependent: purchase decision (need recognition, info search, evaluation, buying, post-purchase). Quantitative associative research targets infinite Bima consumers, sampling 96 via purposive (prior buyers, Bima residents, ≥17 years). Likert data tested validity (r>0.30), reliability (α>0.60), classical assumptions, analyzed by multiple regression SPSS 27. Results: content marketing significantly partial (t=2.639; p=0.010), brand image (t=7.321; p=0.000), simultaneous (R²=54.6%). Conclusion: both drive purchases; recommend creative content enhancement. Keywords: Content Marketing, Brand Image, Purchase Decision, Skintific Cushion.